KEPERCAYAAN MASYARAKAT TERHADAP TRADISI KENDURI POMPONG BARU DI DESA AIR GLUBI KECAMATAN BINTAN PESISIR KABUPATEN BINTAN - Mardiana Mardiana; Sri Wahyuni; Marisa Elsera (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2022)
This study aims to describe how beliefs and what things influence the community so that they still carry out and not carry out the new pompong kenduri tradition for fishermen in Air Glubi Village, Bintan Pesisir District. This research uses a qualitative research method with a descriptive approach. The results of this study showed that there were fishing communities in Air Glubi Village that still and did not practice the new pompong kenduri tradition. People who believe in and perform this new pompong kenduri tradition are influenced by a historical story or past tragedy and the advice of their parents. Moreover, things that affect the community so that they don't carry out traditions because they don't believe in ancestral traditions, developed ways of thinking and there are no legal sanctions. Thus, it is believed that if performing this tradition will have a good impact on their lives but on the contrary, if they don't perform it, it will have a bad impact on their lives.